2021
DOI: 10.1016/s2213-2600(21)00237-x
|View full text |Cite|
|
Sign up to set email alerts
|

Imatinib in patients with severe COVID-19: a randomised, double-blind, placebo-controlled, clinical trial

Abstract: Background The major complication of COVID-19 is hypoxaemic respiratory failure from capillary leak and alveolar oedema. Experimental and early clinical data suggest that the tyrosine-kinase inhibitor imatinib reverses pulmonary capillary leak. Methods This randomised, double-blind, placebo-controlled, clinical trial was done at 13 academic and non-academic teaching hospitals in the Netherlands. Hospitalised patients (aged ≥18 years) with COVID-19, as confirmed by an RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 31 publications
4
75
0
Order By: Relevance
“…Overall, 115 studies with 77,128 patients reported the number of patients requiring mechanical ventilation during the study period. We included ACEIs/ARBs, ammonium chloride, azithromycin, bamlanivimab, baricitinib plus remdesivir, bromhexine, budesonide, camostat mesilate, canakinumab, chloroquine, colchicine, convalescent plasma, dexamethasone, doxycycline, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, imatinib, INM005, interferon beta, intravenous immunoglobulin, ivermectin, lopinavir/ritonavir, methylprednisolone, recombinant human GCSF, remdesivir, sarilumab, sofosbuvir plus daclatasvir, sulodexide, tocilizumab, tofacitinib, vitamin D3 and SOC as treatment nodes in the NMA, for which observations came from 84 studies ( 3 , 6 , 22 26 , 28 31 , 35 , 42 , 43 , 46 , 47 , 50 , 53 , 55 , 57 61 , 63 , 64 , 66 , 67 , 71 , 73 77 , 79 , 80 , 82 , 83 , 85 87 , 89 , 92 94 , 96 100 , 102 , 105 107 , 109 , 111 118 , 120 124 , 126 , 128 132 , 134 , 135 , 139 , 140 , 145 , 151 , 152 , 154 156 ). About one-third (26/84) of the included studies were evaluated as low risk ( Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 115 studies with 77,128 patients reported the number of patients requiring mechanical ventilation during the study period. We included ACEIs/ARBs, ammonium chloride, azithromycin, bamlanivimab, baricitinib plus remdesivir, bromhexine, budesonide, camostat mesilate, canakinumab, chloroquine, colchicine, convalescent plasma, dexamethasone, doxycycline, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, imatinib, INM005, interferon beta, intravenous immunoglobulin, ivermectin, lopinavir/ritonavir, methylprednisolone, recombinant human GCSF, remdesivir, sarilumab, sofosbuvir plus daclatasvir, sulodexide, tocilizumab, tofacitinib, vitamin D3 and SOC as treatment nodes in the NMA, for which observations came from 84 studies ( 3 , 6 , 22 26 , 28 31 , 35 , 42 , 43 , 46 , 47 , 50 , 53 , 55 , 57 61 , 63 , 64 , 66 , 67 , 71 , 73 77 , 79 , 80 , 82 , 83 , 85 87 , 89 , 92 94 , 96 100 , 102 , 105 107 , 109 , 111 118 , 120 124 , 126 , 128 132 , 134 , 135 , 139 , 140 , 145 , 151 , 152 , 154 156 ). About one-third (26/84) of the included studies were evaluated as low risk ( Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The compounds rutin, losartan, imatinib, saquinavir, and tenposide have been seen in other computational screens (Bello et al, 2020;Huynh et al, 2020;Pant et al, 2020;Nejat and Sadt, 2021). Losartan and imatinib have undergone clinical trials with COVID19 patients (Aman et al, 2021;Puskarich et al, 2021). Most of the metabolites found in the computational screens unfortunately were not available for purchase.…”
Section: Results and Discussion Computational Predictionsmentioning
confidence: 99%
“…On the other hand, its antiviral properties have been confirmed in vitro, but subsequent studies have not confirmed its effect on replication or the process of virus penetration into host cells. Further studies on the antiviral mechanism of imatinib are required [62].…”
Section: Preparations Of Indeterminate Mechanism Of Actionmentioning
confidence: 99%